What were you thinking? Decision theory as coherence test - Itzhak Gilboa; Larry Samuelson (Theoretical Economics, 2022)
Decision theory can be used to test the logic of decision making—one may ask whether a given set of decisions can be justified by a decision-theoretic model. Indeed, in principal-agent settings, such justifications may be required—a manager of an investment fund may be asked what beliefs she used when valuing assets and a government may be asked whether a portfolio of rules and regulations is coherent. In this paper we ask which collections of uncertain-act evaluations can be simultaneously justified under the maxmin expected utility criterion by a single set of probabilities. We draw connections to the the Fundamental Theorem of Finance (for the special case of a Bayesian agent) and revealed-preference results.
Keywords: D8; 330; Decision theory; revealed preference; coherence; maxmin expected utility